CHEMICALLY TREATED SISAL FIBER DOPED WITH ALUMINUM NITRATE COMPOSITE - Asif jehan, Dr. shirish joshi & Dr. M.N. Bapat (International Journal of Research Science and Management, 2015)
The current study shows the effect of chemical treatment on the structure and morphology of sisal fibre. In the present study sisal fibre is treated with aluminum nitrate salt. The treatment is done at 1000oC temperature using annealing method. X ray diffraction of the treated sisal fibre reveals the crystalline nature of the fibre. Change in morphology has been found in sisal fibre when subjected to Scanning Electron Microscopy.